2023
DOI: 10.3389/fnut.2022.1057057
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and breast cancer risk, prognosis, and quality of life: A systematic review

Abstract: BackgroundStatistics indicate that the morbidity of breast cancer is increasing globally, and its (overall figures) incidence has now surpassed that of lung cancer for the first time. The relation between a whole dietary pattern, rather than of a single food or nutrient, and breast cancer (BC) should be examined for findings to capture the complexities of diet and the potential for synergism between dietary components. Hence, the effects of dietary patterns on breast cancer have recently attracted increasing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 81 publications
0
1
1
Order By: Relevance
“…Our results of a null association between adherence to the DASH diet and breast cancer risk are not in line with the results of two systematic reviews [36,37], showing how greater adherence to the DASH dietary model was inversely associated with the risk of developing breast cancer [38]. This may be due to the fact that the DASH diet has traditionally been studied for the American population, whose eating habits and dietary survey and assessment tools are different from those used in this study.…”
Section: Discussioncontrasting
confidence: 89%
“…Our results of a null association between adherence to the DASH diet and breast cancer risk are not in line with the results of two systematic reviews [36,37], showing how greater adherence to the DASH dietary model was inversely associated with the risk of developing breast cancer [38]. This may be due to the fact that the DASH diet has traditionally been studied for the American population, whose eating habits and dietary survey and assessment tools are different from those used in this study.…”
Section: Discussioncontrasting
confidence: 89%
“…Several studies have reported that eating more dietary fiber from various sources including whole grains, pulses, vegetables, and fruits can supply essential nutrients and antioxidants that bolster overall health and not only reduce the risk of BC in men but also improve the overall survival (OS) rate. 48 51 Incorporation of a diverse array of colors with a wide spectrum of essential nutrients could ensure prevention of BC. 52 Lean proteins sourced from poultry, fish, beans, lentils, and tofu provide essential amino acids necessary for cellular repair and maintenance.…”
Section: Introductionmentioning
confidence: 99%